Remittances, terrorism, and democracy - Park, Yohan (My University, 2024)
How do remittances affect domestic terrorism? Past work argues that remittances increase groups’ resources and increase terrorism. However, we argue that the effect of remittances depends on political institutions. Within democracies, remittances can help groups overcome barriers to legitimate politics and reduce terrorism’s allure. Within autocracies, however, fewer legitimate political opportunities exist, and remittances may lead to more terrorism as it remains an alternative and available political outlet. We find that remittances are associated with less (more) domestic terrorism within democracies (autocracies) and use additional mechanism tests to demonstrate that the competitive aspects of democracy help explain these trends.
PUBLISHED
https://doi.org/10.1177/07388942231207029
Keywords: Conflict/Dispute Resolution; DEMOCRACY; International economics, finance, trade and development